Assessment of Quality Indicators in Cytopathology – Measuring What Matters - Shah, Khushbu Mehulkumar; Kher, Sheetal D; Agrawal, Utkarsh V; Singh, Ritu R; Shah, Vishal A (Annals of Pathology and Laboratory Medicine, 2024)
Background: Laboratories play a crucial role in diagnosis and patient care. It is vital to assess, quantify, and improve the quality of laboratory functioning through continuous monitoring. This requires periodic evaluation of well-defined Quality Indicators (QI). The aim of this study was to evaluate and analyze QI in the department of cytopathology. Materials and Methods: This retrospective descriptive study of one-year duration (1st July 2022 to 30th June 2023) was carried out in the Cytopathology section. Eleven QI were analyzed for all phases (pre-analytical, analytical, and post-analytical) of testing processes. The results were noted in terms of numbers, percentages, and ratios. Results: In the pre-analytical phase, repeat FNACs were 11.5%, and the overall assessment of staining quality was found to be satisfactory. In the analytical phase, inconclusive diagnoses were 6.46%, positivity rates for the PAP test were 8.4%, ASC-US/SIL ratio was 2:1, and AUS: Malignant ratio in thyroid cytopathology was 5:1. The results of EQAS cycles were within consensus in 88% of cases, while discordance in cytopathology and histopathology correlation was noted in 3.33% of cases. In the post-analytical phase, the number of reports exceeding the defined TAT (turnaround time) was found to be 1.5%. Conclusion: Continuous improvement of quality in laboratories requires monitoring in the form of QI. Assessment and analysis of QI is an effective tool to improve quality in cytopathology. Well-defined QI should be prepared for all aspects of laboratory work and periodically analyzed for monitoring and continuous improvement.